Optimasi Website Sekolah Dasar Sebagai Media Publikasi Informasi Untuk Meningkatkan Daya Saing - Noordin Asnawi; Ridho Pamungkas; Fawwaz Naufaldini (Pusat Riset dan Inovasi Nasional, 2023)
Fast-developing technology has changed many work processes in various fields to digital, including the field of education. Currently various school information can be accessed easily with the existence of internet technology through the school website. With the existence of a school website, it can be used as a means of disseminating information, promotional media, and so on. MI Muhammadiyah Madiun City already has a school website, but the function of the website has not been optimized to help and facilitate school needs. Therefore, this training activity is needed to provide insight and training on using the school's website to be more optimal. The training participants were 12 teachers at MI Muhammadiyah Madiun City. From the results of the training, the participants were very enthusiastic about undergoing the training to be able to manage the school's website and promote their school through each teacher's social media.